2001
DOI: 10.1074/jbc.m008392200
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-induced Dynamic Membrane Changes and Cell Deletion Conferred by Vanilloid Receptor 1

Abstract: The real time dynamics of vanilloid-induced cytotoxicity and the specific deletion of nociceptive neurons expressing the wild-type vanilloid receptor (VR1) were investigated. VR1 was C-terminally tagged with either the 27-kDa enhanced green fluorescent protein (eGFP) or a 12-amino acid ⑀-epitope. Upon exposure to resiniferatoxin, VR1eGFP-or VR1⑀-expressing cells exhibited pharmacological responses similar to those of cells expressing the untagged VR1. Within seconds of vanilloid exposure, the intracellular fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
264
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(273 citation statements)
references
References 39 publications
9
264
0
Order By: Relevance
“…RTX is a well-known capsaicin analogue, and its binding is competitively inhibited by the TRPV1 antagonist capsazepine (Szallasi and Blumberg, 1999). RTX treatment can activate TRPV1 and rapidly kill primary afferent neurons through calcium influx and overloading (Olah et al, 2001;Wu et al, 2005). Our immunocytochemistry data confirmed that RTX eliminated presynaptic δ-opioid receptors on TRPV1-immunoreactive DRG neurons and their terminals in the spinal dorsal horn.…”
Section: Discussionsupporting
confidence: 67%
“…RTX is a well-known capsaicin analogue, and its binding is competitively inhibited by the TRPV1 antagonist capsazepine (Szallasi and Blumberg, 1999). RTX treatment can activate TRPV1 and rapidly kill primary afferent neurons through calcium influx and overloading (Olah et al, 2001;Wu et al, 2005). Our immunocytochemistry data confirmed that RTX eliminated presynaptic δ-opioid receptors on TRPV1-immunoreactive DRG neurons and their terminals in the spinal dorsal horn.…”
Section: Discussionsupporting
confidence: 67%
“…TRPV3 appears to exhibit a similar pattern in skin sections (3), a result we have confirmed. 3 Functional intracellular TRPV1 has been detected in sensory neurons (33)(34)(35) and heterologously transfected cells (36). In urinary epithelial cells, TRPV1 immunoreactivity has also been detected in an intracellular, apparently vesicular compartment (37).…”
Section: Discussionmentioning
confidence: 95%
“…DRG Cultures. Pregnant female rats or mice were killed, and embryos were removed from the uterus at embryonic day 15 (39). Cells were dissociated with 0.125% trypsin͞EDTA in Ca 2ϩ ͞Mg 2ϩ -free Hanks' balanced salt solution (HBSS) for 30 min at 35°C, and an aliquot was stained with trypan blue to count the viable cells.…”
Section: Methodsmentioning
confidence: 99%